MAYBE Initial complexity problem: 1: T: (1, 1) f20(a, b) -> f1(0, 0) (?, 1) f1(a, b) -> f1(a + 1, b + 1) (?, 1) f1(a, b) -> f30(a, b) [ a >= b + 1 ] start location: f20 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (1, 1) f20(a, b) -> f1(0, 0) (?, 1) f1(a, b) -> f1(a + 1, b + 1) start location: f20 leaf cost: 1 Applied AI with 'oct' on problem 2 to obtain the following invariants: For symbol f1: X_1 - X_2 >= 0 /\ X_2 >= 0 /\ X_1 + X_2 >= 0 /\ -X_1 + X_2 >= 0 /\ X_1 >= 0 This yielded the following problem: 3: T: (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] (1, 1) f20(a, b) -> f1(0, 0) start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(0, 0) with all transitions in problem 3, the following new transition is obtained: f20(a, b) -> f1(1, 1) [ 0 >= 0 ] We thus obtain the following problem: 4: T: (1, 2) f20(a, b) -> f1(1, 1) [ 0 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(1, 1) [ 0 >= 0 ] with all transitions in problem 4, the following new transition is obtained: f20(a, b) -> f1(2, 2) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 ] We thus obtain the following problem: 5: T: (1, 3) f20(a, b) -> f1(2, 2) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(2, 2) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 ] with all transitions in problem 5, the following new transition is obtained: f20(a, b) -> f1(3, 3) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 ] We thus obtain the following problem: 6: T: (1, 4) f20(a, b) -> f1(3, 3) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(3, 3) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 ] with all transitions in problem 6, the following new transition is obtained: f20(a, b) -> f1(4, 4) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 ] We thus obtain the following problem: 7: T: (1, 5) f20(a, b) -> f1(4, 4) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(4, 4) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 ] with all transitions in problem 7, the following new transition is obtained: f20(a, b) -> f1(5, 5) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 ] We thus obtain the following problem: 8: T: (1, 6) f20(a, b) -> f1(5, 5) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(5, 5) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 ] with all transitions in problem 8, the following new transition is obtained: f20(a, b) -> f1(6, 6) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 ] We thus obtain the following problem: 9: T: (1, 7) f20(a, b) -> f1(6, 6) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(6, 6) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 ] with all transitions in problem 9, the following new transition is obtained: f20(a, b) -> f1(7, 7) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 ] We thus obtain the following problem: 10: T: (1, 8) f20(a, b) -> f1(7, 7) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(7, 7) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 ] with all transitions in problem 10, the following new transition is obtained: f20(a, b) -> f1(8, 8) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 ] We thus obtain the following problem: 11: T: (1, 9) f20(a, b) -> f1(8, 8) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(8, 8) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 ] with all transitions in problem 11, the following new transition is obtained: f20(a, b) -> f1(9, 9) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 ] We thus obtain the following problem: 12: T: (1, 10) f20(a, b) -> f1(9, 9) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(9, 9) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 ] with all transitions in problem 12, the following new transition is obtained: f20(a, b) -> f1(10, 10) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 ] We thus obtain the following problem: 13: T: (1, 11) f20(a, b) -> f1(10, 10) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(10, 10) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 ] with all transitions in problem 13, the following new transition is obtained: f20(a, b) -> f1(11, 11) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 ] We thus obtain the following problem: 14: T: (1, 12) f20(a, b) -> f1(11, 11) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(11, 11) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 ] with all transitions in problem 14, the following new transition is obtained: f20(a, b) -> f1(12, 12) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 /\ 11 >= 0 /\ 22 >= 0 ] We thus obtain the following problem: 15: T: (1, 13) f20(a, b) -> f1(12, 12) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 /\ 11 >= 0 /\ 22 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(12, 12) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 /\ 11 >= 0 /\ 22 >= 0 ] with all transitions in problem 15, the following new transition is obtained: f20(a, b) -> f1(13, 13) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 /\ 11 >= 0 /\ 22 >= 0 /\ 24 >= 0 ] We thus obtain the following problem: 16: T: (1, 14) f20(a, b) -> f1(13, 13) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 /\ 11 >= 0 /\ 22 >= 0 /\ 24 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(13, 13) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 /\ 11 >= 0 /\ 22 >= 0 /\ 24 >= 0 ] with all transitions in problem 16, the following new transition is obtained: f20(a, b) -> f1(14, 14) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 /\ 11 >= 0 /\ 22 >= 0 /\ 24 >= 0 /\ 13 >= 0 /\ 26 >= 0 ] We thus obtain the following problem: 17: T: (1, 15) f20(a, b) -> f1(14, 14) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 /\ 11 >= 0 /\ 22 >= 0 /\ 24 >= 0 /\ 13 >= 0 /\ 26 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 By chaining the transition f20(a, b) -> f1(14, 14) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 /\ 11 >= 0 /\ 22 >= 0 /\ 24 >= 0 /\ 13 >= 0 /\ 26 >= 0 ] with all transitions in problem 17, the following new transition is obtained: f20(a, b) -> f1(15, 15) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 /\ 11 >= 0 /\ 22 >= 0 /\ 24 >= 0 /\ 13 >= 0 /\ 26 >= 0 /\ 28 >= 0 ] We thus obtain the following problem: 18: T: (1, 16) f20(a, b) -> f1(15, 15) [ 0 >= 0 /\ 1 >= 0 /\ 2 >= 0 /\ 4 >= 0 /\ 3 >= 0 /\ 6 >= 0 /\ 8 >= 0 /\ 5 >= 0 /\ 10 >= 0 /\ 12 >= 0 /\ 7 >= 0 /\ 14 >= 0 /\ 16 >= 0 /\ 9 >= 0 /\ 18 >= 0 /\ 20 >= 0 /\ 11 >= 0 /\ 22 >= 0 /\ 24 >= 0 /\ 13 >= 0 /\ 26 >= 0 /\ 28 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b + 1) [ a - b >= 0 /\ b >= 0 /\ a + b >= 0 /\ -a + b >= 0 /\ a >= 0 ] start location: f20 leaf cost: 1 Complexity upper bound ? Time: 0.707 sec (SMT: 0.652 sec)